THE INFLUENCE OF AUDITOR ETHICS, AUDIT FEE, AND AUDITOR MOTIVATION ON AUDIT QUALITY IN PUBLIC ACCOUNTING - Zurriah, Rezki (International Proceeding of Law and Economic, 2021)
This study aims to determine the effect of auditor ethics, audit fees, and auditor motivation on audit quality either partially or simultaneously. This study uses an associative research approach, namely research that aims to analyze the relationship between one variable and other variables or how one variable affects other variables. The population in this study are auditors who work at the Public Accounting Firm in Medan City. Sampling in this study used the Saturated Sampling technique. Data collection techniques in this study by distributing questionnaires to research respondents. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that simultaneously auditor ethics, audit fees, and auditor motivation have a significant effect on audit quality with an F-test significance value of 0.000. Partially, auditor ethics and audit fees have a significant effect on audit quality with t-test significance values ​​of 0.033 and 0.004 respectively. Meanwhile, the auditor's motivation partially has no significant effect on audit quality with a t-test significance value of 0.397.